Optimización del llenado de botellones en la planta de agua de la Facultad de Ingeniería Química de la Universidad Nacional de la Amazonía Peruana mediante un sistema automatizado - Ferry Martínez, José Javier (2024)
This thesis had as its general objective: to optimize the filling of bottles in the Water Plant of the Faculty of Chemical Engineering of the National University of the Peruvian Amazon, for which an automated system was implemented, consisting of 3 electrovalves, an electropump, a PLC, 3 pushbuttons, 4 leds, and a thermal switch with its bipolar plug. The PLC used is the Siemens (LOGO! 230RC 6ED1 052-1FB00-0BA6), whose programming was done using the LOGO!Soft Comfort V6.1 software, which consisted of developing a control algorithm consisting of 28 elements: 3 internal coils, 4 exits, 3 timers, 17 contacts, and a counter. To verify if the automated system works efficiently, 20 bottles were selected, which had a theoretical volume of 19 L. The flows generated by the filling electropump through electrovalves 1, 2, and 3 were: 0.617 L/s, 0.633 L/s, and 0.632 L/s, respectively. In the same order, the times that electrovalves 1, 2, and 3 had to be turned on to fill the bottles were: 30.8 s, 30.0 s, and 30.1 s. In the 20 bottles, the difference between the theoretical volume and the experimental volume did not exceed 2 % of the theoretical volume; thus proving that the efficiency of the system is greater than 98 % and therefore the filling of bottles is optimal. This thesis concludes by achieving the general objective and proving the corresponding hypothesis